КОММУНИКАТИВНАЯ ВИРТУАЛЬНАЯ ИДЕНТИЧНОСТЬ: ГЕНДЕРНЫЙ АНАЛИЗ (Filološke pripombe, 2019)
The paper enlightens Computer-Mediated (Internet) Communication and virtual communicative identity resulted by CMC. The special stress is done on the gender virtual identity as a one of basic components of social identity. Additionally the methodology of virtual gender identity research is under review. The psycholinguistic techniques are suggested for the communicative virtual identity research including the gender one.